Incidence and morphological characterization of rhizoctonia solani kuhn on durian (Durio Zibethinus Murr.) seedlings in Tugbok District, Davao City - Labradores, Angelica Mary Joan A. (2010)
The objectives of this study is to determine the incidence of Rhizoctonia solani on durian seedlings, describe its cellular and colonial morphology and study its colonial growth under various light regimes, pH levels and temperatures, in vitro. Observation of Rhizoctonia disease on durian seedlings was conducted at Alcon farm, Tugbok District, Davao City from June 28, 2009 to December 28, 2009. Initial population of the seedlings was recorded and infected seedlings were separated from the rest of the seedlings weekly. Symptoms show irregular brown patches with dark brown margins on the leaves; the mycelium spreads to adjoining leaves; and sometimes, leaf drop and twig dieback occur. Isolation to pure culture and pathogenecity test were conducted using Photo Dextrose Agar (PDA) plates for stock cultures. Hyphal length is 28.82+-7.726223 um and hyphal width is 2.9+-0.631177 um. 30 PDA plates laced with 200 ppm streptomycin were exposed in three light regimes: T1-continuos light, T2-alternating 12 hour darkness and 12 hour light and T3 - continuous darkness with 10 replicates per treatment and incubated for 7 days. Another set of 30 plates of R. solani were incubated into PDA plates for 7 days with varying pH levels: T1-7, T2-6 and T3-5. Another set of 20 plates with fungal cultures were incubated for 7 days under different temperatures: T1 - air conditioned temperature (22+-2'C) and T2- Room temperature (27+-2'C). The colony growth under pH 7 showed a significant from those under pH 6 and 5 on the 3rd day but showed no difference after the 7th day of incubation. These show the mesophilic and acidophilic characteristics of R. solani under various temperatures and pH levels.
Thesis (BS Biology) -- University of the Philippines Mindanao, 2010
Keywords: Rhizoctonia solani; Incidence; Durio zibethinus; Durian seedlings